Advances in Multi-Functional Ligands and the Need for Metal-Related Pharmacology for the Management of Alzheimer Disease - Sharma, Abha; Pachauri, Vidhu; Flora, S. J. S. (Frontiers in Pharmacology, 2018)
Alzheimer’s disease (AD) is the age linked neurodegenerative disorder with no disease modifying therapy currently available. The available therapy only offers short term symptomatic relief. Several hypotheses have been suggested for the pathogenesis of the disease while the molecules developed as possible therapeutic agent in the last decade, largely failed in the clinical trials. Several factors like tau protein hyperphosphorylation, amyloid-β (Aβ) peptide aggregation, decline in acetyl cholinesterase and oxidative stress might be contributing towards the pathogenesis of AD. Additionally, biometals dyshomeostasis (Iron, Copper, and Zinc) in the brain are also reported to be involved in the pathogenesis of AD. Thus, targeting these metal ions may be an effective strategy for the development of a drug to treat AD. Chelation therapy is currently employed for the metal intoxication but we lack a safe and effective chelating agents with additional biological properties for their possible use as multi target directed ligands for a complex disease like AD. Studies indicate that many chelating agents are able to disaggregate Aβ aggregation, dissolving amyloid plaques, to delay the cognitive impairment. Thus there is an urgent need to develop disease modifying therapeutic molecules with multiple beneficial features like targeting more than one factor responsible of the disease. These molecules, as disease modifying therapeutic agents for AD, should possess the potential to inhibit Aβ-metal interactions, the formation of toxic Aβ aggregates; and the capacity to reinstate metal homeostasis.